ASSESSING RESPIRATORY FITNESS AND DIAPHRAGM EXCURSION IN POSTPARTUM WOMEN WITH MECHANICAL LOW BACK PAIN: A NARRATIVE REVIEW - BENAZIR BASHIR; RAMESH CHANDRA PATRA; BHAWNA KUMARI; ASILU MITTI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Postpartum lower back pain, a multifaceted concern affects a significant proportion of women during the initial six weeks following childbirth. This narrative review explores the interplay between respiratory fitness, diaphragm excursion, and mechanical low back pain in postpartum women, illuminating a complex and underexplored relationship. The postpartum phase, characterized by profound physiological adaptations, underscores the need to scrutinize the role of respiratory fitness and diaphragmatic function in the context of women’s health. While research in this area is limited, emerging evidence suggests potential connections between diaphragm dysfunction and LBP, necessitating further investigation. This review emphasizes the broader implications of postpartum LBP, extending beyond physical discomfort to impact emotional and psychological well-being. Despite certain limitations, this narrative synthesis provides a foundation for future research, advocating for longitudinal studies and interventional approaches to address postpartum LBP comprehensively. It calls for a holistic perspective, recognizing the pivotal role of respiratory fitness in the well-being of postpartum women, allowing them to fully embrace the transformative journey of motherhood.